2003
DOI: 10.1007/s00436-003-0838-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic response of Brugia pahangi infective larvae to jird serum in vitro

Abstract: The Brugia pahangi infective larval response to jird serum was studied using an agar plate assay. Larvae placed onto the agar remained at the same place for 60 min. Once the larvae were stimulated by serum, more than 95% oriented towards the serum and reached it within few minutes. This larval response was inhibited by an activator of phosphodiesterase (imidazole), adenylate cyclase inhibitors (SQ22536 and MDL-12330A) and protein kinase A inhibitor. An inhibitor of phosphodiesterase (IBMX), an activator of ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Filariae are also skin-penetrating parasitic nematodes, and their infection of hosts involves a chemotactic response. Recent studies (Gunawardena et al, 2003;Kusaba et al, 2008) have suggested that mammalian sera contain a chemoattractant for B. pahangi L3. Since these studies, however, there has been little progress in investigations regarding the attractants of B. pahangi L3.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Filariae are also skin-penetrating parasitic nematodes, and their infection of hosts involves a chemotactic response. Recent studies (Gunawardena et al, 2003;Kusaba et al, 2008) have suggested that mammalian sera contain a chemoattractant for B. pahangi L3. Since these studies, however, there has been little progress in investigations regarding the attractants of B. pahangi L3.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure previously described by Gunawardena et al (2003) applied HBSS to the I-area where filarial L3 were inoculated ( fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations